Negosiasi Kesalehan dan Representasi Simbolik dalam Praktik Umrah Generasi Z di Era Media Sosial - Lyra Ella Sepfira; Faisal Riza (Islam & Contemporary Issues, 2026)
This study explores how Generation Z negotiates religious devotion and symbolic self-representation in the contemporary practice of umrah within digital culture. The research focuses on two central issues: the ways Gen Z interprets umrah as a spiritual journey and how religious intentions are balanced with the desire for online visibility. Employing a qualitative phenomenological approach, the study involved three Generation Z informants selected purposively based on their umrah experiences and social media engagement. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that umrah continues to function as a deeply personal religious experience that encourages spiritual reflection, emotional awareness, and behavioral transformation. At the same time, the ritual is also presented selectively through social media as part of identity construction and symbolic communication in digital spaces. This study contributes theoretically to discussions on digital religiosity by demonstrating that piety and symbolic expression among Generation Z are not mutually exclusive; instead, both are continuously negotiated within the intersection of spirituality, self-identity, and online culture in contemporary Muslim society.